2013
DOI: 10.1016/j.ajhg.2013.04.022
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in POFUT1, Encoding Protein O-fucosyltransferase 1, Cause Generalized Dowling-Degos Disease

Abstract: Dowling-Degos disease (DDD), or reticular pigmented anomaly of the flexures, is a type of rare autosomal-dominant genodermatosis characterized by reticular hyperpigmentation and hypopigmentation of the flexures, such as the neck, axilla, and areas below the breasts and groin, and shows considerable heterogeneity. Loss-of-function mutations of keratin 5 (KRT5) have been identified in DDD individuals. In this study, we collected DNA samples from a large Chinese family affected by generalized DDD and found no mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 37 publications
6
134
1
6
Order By: Relevance
“…12 Additionally, recent studies of two Chinese families with DDD led to the identification of mutations in POFUT1 (MIM 607491), which encodes protein O-fucosyltransferase 1 from the Notch pathway. 13 Here, we describe the identification of nine different mutations in POGLUT1 (RefSeq accession number NM_152305.2) from 13 unrelated individuals with DDD. POGLUT1 encodes protein O-glucosyltransferase 1 and is a part of the Notch signaling pathway.…”
Section: Dowling-degos Disease (Ddd [Mim 179850 Mim 615327])mentioning
confidence: 99%
“…12 Additionally, recent studies of two Chinese families with DDD led to the identification of mutations in POFUT1 (MIM 607491), which encodes protein O-fucosyltransferase 1 from the Notch pathway. 13 Here, we describe the identification of nine different mutations in POGLUT1 (RefSeq accession number NM_152305.2) from 13 unrelated individuals with DDD. POGLUT1 encodes protein O-glucosyltransferase 1 and is a part of the Notch signaling pathway.…”
Section: Dowling-degos Disease (Ddd [Mim 179850 Mim 615327])mentioning
confidence: 99%
“…Patients with Dowling-Degos disease are characterized by the typical reticulated hyper- and/or hypopigmentation in the flexural regions [16], which were not seen in our patients. Further genetic studies on the reported POFUT1 mutations encoding protein O-fucosyltransferase 1 can further exclude the diagnosis [17]. The absence of contact history to dioxins and of atrophy of the sebaceous gland in histology makes the diagnosis of MADISH unlikely [18].…”
Section: Discussionmentioning
confidence: 99%
“…All three enzymes modify multiple EGF repeats in the extracellular domain of the Notch receptor (12)(13)(14), and these modifications are essential for optimal Notch activity (15)(16)(17). Human diseases result from inactivating mutations in these enzymes and appear to be mediated by reduced Notch function (17)(18)(19)(20). O-Glucose can be elongated by xylosyltransferases (GXYLT1/2 and XXYLT1) to form the trisaccharide Xyl␣1-3Xyl␣1-3Glc, and O-fucose can be elongated by Fringe enzymes (LFNG, MFNG, and RFNG) to ultimately form the tetrasaccharide Sia␣2-6Gal␤1-4GlcNAc␤1-3Fuc (21)(22)(23)(24).…”
mentioning
confidence: 99%